Results of late surgical intervention in children with early-onset bilateral cataracts - Ganesh, Suma (Br J Ophthalmol, 2014)
BACKGROUND: Cataracts are a major cause of childhood blindness globally. Although surgically treatable, it is unclear whether children would benefit from such interventions beyond the first few years of life, which are believed to constitute `critical' periods for visual development. AIMS: To study visual acuity outcomes after late treatment of early-onset cataracts and also to determine whether there are longitudinal changes in postoperative acuity. METHODS: We identified 53 children with dense cataracts with an onset within the first half-year after birth through a survey of over 20 000 rural children in India. All had accompanying nystagmus and were older than 8 years of age at the time of treatment. They underwent bilateral cataract surgery and intraocular lens implantation. We then assessed their best-corrected visual acuity 6 weeks and 6 months after surgery. RESULTS: 48 children from the pool of 53 showed improvement in their visual acuity after surgery. Our longitudinal assessments demonstrated further improvements in visual acuity for the majority of these children proceeding from the 6-week to 6-month assessment. Interestingly, older children in our subject pool did not differ significantly from the younger ones in the extent of improvement they exhibit. CONCLUSIONS AND RELEVANCE: Our results demonstrate that not only can significant vision be acquired until late in childhood, but that neural processes underlying even basic aspects of vision like resolution acuity remain malleable until at least adolescence. These data argue for the provision of cataract treatment to all children, irrespective of their age.